Сценарии организации цифровых трактов для ВЧ-связи по высоковольтным линиям электропередачи - Kuricyn, E. M.; Panteleev, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Scenarios are considered for building a unified high‑speed access network with service integration (ISAN — Integrated Services Access Network) over the high‑voltage transmission lines of the United Energy System of Ukraine, within the corporate network of the National Energy Company “Ukrenergo.”